Modeling of microstructure evolution during high-temperature oxidation of porous Fe-Cr steels - Samih Haj Ibrahim; Damian Koszelow; Małgorzata Makowska; Sebastian Molin (Materials & Design)
Research on the high-temperature oxidation of metals and alloys is experimentally challenging due to the requirement for long-term corrosion exposure, and in the case of porous alloys, due to their complex internal microstructure. In this study, a corrosion model based on the morphological operations of dilation and erosion has been developed. This approach allows for a utilization of various raster representations of the microstructure as input to investigate the microstructure evolution of porous alloys during the corrosion process. Herein, porous microstructures of the porous Fe-Cr steels obtained from SEM imaging, X-ray tomography, and artificial 3D models generated with the use of Generative Adversarial Networks were used as test cases. The obtained results demonstrated high compliance with the experimental evaluation of porosity evolution and chromium content decrease during oxidation at 700 °C for 3000 h. Additionally, new material microstructures were studied and the influence of initial porosity on the chromium content depletion and alloy lifetime during long-term oxidation was revealed.